The gyepű as cultural landscape type in Székelyföld - Ambrus, Tünde (JOURNAL OF LANDSCAPE ECOLOGY, 2009)
The landscape evaluation of Székelyföld can not be interpreted without the examination of the historical function. However with the lack of the historical source documents it is very hard to provide a unambiguous answer to the creation of the “tízesek” connected to the “gyepű” system. It is complicated to punctually reconstruct that unique settlement structure which the historical era’s military technique exacted for the settlement. It is not by chance that from the previous century till present days the historical, ethnographic monographs and travel books only mention them on account of the Székely people. But by all means the researchers should have been aware of the importance of the knowledge connected to the “tízesek” and their oblivion as well. The results of the empirical research with the assistance of the disposable literature maps, and qualitative and quantitative data collecting methods proved that the “tízesek” determined the most important phases of landscape genesis and determine the basic landscape structure till recent days. The citizens transmitted the ancient remnants of their military organisation, lifestyle traditions and habits. Since the rhythm of the present era endangers the thinking, landscape protection and utilisation of the Székely people, it is important to keep count of and review the example – which is the result of symbiosis of discipline, reasoning and activity – of the predecessors creating this system. It is not about the restoration of a romantic village structure, the subsistence of the village “tízesek” is asserted by a social-economic-political frame necessity. Because of the diminution of the historical cultural landscape elements and items, uniqueness becomes a more and more important appreciation factor. So the “Székely tízesek” preserving the characteristic memories of the “gyepű” and the connected cultural historical values from the point of view of heritage planning become more and more important and more and more valuable from the point of view of landscape exploitation.
Keywords: “gyepű” system; settlement structure; „tízesek”; mental space; heritage protection; landscape exploitation